Excitation device for mining steel wire rope based on magnetic flux leakage detection - LI Jianhui; SUN Xianbin; LIU Lunming; CHEN Rongxin; ZHAN Weixia (Gong-kuang zidonghua, 2023)
The current research does not consider the influence of wire rope swing on the excitation device in the context of engineering applications, resulting in unsatisfactory detection results. In order to solve this problem, a set of mining wire rope excitation devices has been designed. Through the establishment of the wire rope simulation model, the influence of different air gap and lift off value on the magnetic leakage field of wire rope is simulated and studied. It is found that increasing the air gap or lift off value will reduce the magnetic induction intensity of the magnetic leakage field of the wire rope and affect the magnetic leakage detection results of the wire rope. However, in practical applications, the swing amplitude of mining wire ropes is large and the ropes are easy to be polluted. Therefore, the air gap and lift off value of the wire rope excitation device should not be too small. Under the conditions of considering engineering applicability, the air gap is set to 6 mm and the lift off value is set to 5 mm. Further simulation analysis is conducted on the effects of permanent magnet thickness and length, magnetic pole spacing, and armature thickness on the leakage magnetic field of steel wire ropes. It is found that the thickness and length of permanent magnets have the greatest influence on the leakage magnetic field of steel wire ropes. The magnetic pole spacing has a small influence on the leakage magnetic field of steel wire ropes. The influence of armature thickness on the leakage magnetic field of steel wire ropes can be ignored. Based on the simulation results and considering economy and portability, the parameters of the wire rope excitation device are set. The permanent magnet thickness is set to 10 mm, the permanent magnet length is set to 30 mm, the magnetic pole spacing is set to 180 mm, and the armature thickness is set to 10 mm. The dynamic simulation results show that the peak-to-peak value of the magnetic flux density of the wire rope magnetic leakage field reaches 0.9 mT. It indicates that the excitation device can ensure high magnetic leakage at the damage. The experimental results show that the magnetic flux leakage signal shows significant fluctuations at different broken wire locations of the steel wire rope. It indicates that the excitation device has a good excitation effect and can accurately detect broken wire damage of the steel wire rope.